THE EFFECT OF SEPARATION OF INITIAL ASSESSMENT DOCUMENTS ON THE LENGTH OF STAY IN EMERGENCY INSTALLATION IN KENDARI CITY GENERAL HOSPITAL: SEPARATION OF INITIAL ASSESSMENT DOCUMENTS - Tono Sumanto; Sunarsih Sunarsih; Timbul Supodo (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: A preliminary survey of prospective researchers in  the Kendari City General Hospital especially in the Emergency Installation (ER), the number of emergency room visits has decreased in the last 3 years, in 2017 the total number of patients treated in the ER was 10.869 patients, then in 2018 the number of visits decreased to 10.768 patients, and in 2019 the number of visits fell to 9.747 patients. Meanwhile, based on the data in the last few months in 2020 there was a very large spike in decline in the last month, in January 2020 the number of patient who visited,  were  849 people, then in February 2020 the number of the patient were  1202 patients, March 2020 the number of visits was 1216 patients and finally in April 2020 it fell to 451 people. The purpose of this study is to analyse the effect of separation of the initial assessment documents on Length of Stay in Emergency Installation in Kendari City General Hospital. Methods: The research design was experimental with design pretest post-test one group design. The research location was in the Emergency Room of the Kendari City Regional General Hospital which was carried out during February 2021. The population of all patients who were hospitalized was> 17 years old while the sample was 18 people with the sampling technique of separated random sampling. Result: This study found separation of the initial assessment documents affected significantly to  Length of Stay patients in Emergency room in Kendari City General Hospital (p- value =  0.045 < 0.05). Conclusion: Separation technique of the initial assessment documents on Length of Stay was effective to reduce the Length of Stay patients in Emergency room in Kendari City Hospital.